Patterns of microplastic incorporation in larval and pupal cases of Limnephilus hamifer (Trichoptera: Limnephilidae) - Arias-Paco, Andrés (2025)
Introduction: Microplastics (MPs) are an omnipresent problem in the environment. However, research on the effects of microplastics on invertebrate organisms in freshwater ecosystems is relatively limited. Objective: Our aim is to study the patterns of incorporation of MPs by Trichoptera larvae in the Neotropics. Methods: We collected 30 fourth and fifth instar larvae of Limnephilus hamifer from Cerro de la Muerte, Costa Rica (2 764 m.a.s.l.) and transferred them to the laboratory, where we acclimatized them for 72 hours. We induced the larvae to leave their natural cases and deposited five in each of the following treatments: 100 % MPs, 75 % MPs, 50 % MPs, 25 % MPs and 0 % MPs, where the rest of the percentage corresponded to organic matter from the same collection site. In a sixth treatment, we deposited five larvae with their original cases on a 50 % MPs substrate. The MPs consisted of a proportional mixture of PET of four colors: orange, blue, green and transparent. Results: We found that larvae from all treatments constructed their cases incorporating MPs, even when organic matter was available. In general, the cases made with MPs had a higher weight than the natural cases and those of the control group. Additionally, we observed that orange-colored MPs were more incorporated into the cases in all treatments, so possibly Trichoptera larvae have preferences towards the orange color. We also observed the incorporation of MPs in larvae with their original cases, and notably, we recorded the incorporation of MPs in pupal cases, something not reported in the literature at the moment. Conclusions: The incorporation of MPs in all treatments has important consequences because they can accumulate toxins that affect the organisms. The fact that MPs cases are heavier than natural ones could mean a problem in the mobility of the larvae on the substrate, which leads to a greater energetic wear. Finally, incorporating MPs into fixed structures such as pupal cases may make them more conspicuous to visual predators such as fish.